2021
DOI: 10.3389/fphar.2021.632767
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology, Toxicity, Bioavailability, and Formulation of Magnolol: An Update

Abstract: Magnolol (MG) is one of the primary active components of Magnoliae officinalis cortex, which has been widely used in traditional Chinese and Japanese herbal medicine and possesses a wide range of pharmacological activities. In recent years, attention has been drawn to this component due to its potential as an anti-inflammatory and antitumor drug. To summarize the new biological and pharmacological data on MG, we screened the literature from January 2011 to October 2020. In this review, we provide an actualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 162 publications
1
34
0
Order By: Relevance
“…Magnolol is another important compound in the lignan class that is extracted from Magnolia officinalis [ 144 ]. Magnolol significantly attenuated body weight and muscle weight loss in cisplatin-induced sarcopenic mice.…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…Magnolol is another important compound in the lignan class that is extracted from Magnolia officinalis [ 144 ]. Magnolol significantly attenuated body weight and muscle weight loss in cisplatin-induced sarcopenic mice.…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…In the present study, co-amorphous curcumin-magnolol was designed based on their solubility/dissolution defects and potential drug combination advantages. Curcumin (CUR, Figure 1 a) and magnolol (MAG, Figure 1 b) have gained increasing interest because of their multiple biological activities (such as antioxidant, anticancer, antimicrobial, and anti-inflammatory) [ 19 , 20 , 21 , 22 , 23 ]. Moreover, the two drugs have generated combined therapeutic effects in cardiovascular diseases, Alzheimer’s disease, and neurodegenerative diseases [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review regarding numerous properties of magnolol as well as its bioavailability, toxicity and pharmacology has been recently published by Lin Yiping [ 18 ]. Nevertheless, our work primarily focuses on the influence of magnolol on glucose homeostasis and glycemic control, as well as its effect on disrupted lipid metabolism in the course of diabetes and the neutralization of the effects of diabetic complications in various organs.…”
Section: Magnolol—a Brief Description Of a Chemical Compound Its Occurrence In Nature And The Most Important Activitiesmentioning
confidence: 99%
“…To the best of our knowledge, there are currently no studies describing the neuroprotective properties of magnolol in relation to degenerative changes occurring in the course of diabetes mellitus such as neuropathy, disorders of autonomic functions or the diabetic foot. Despite the lack of studies on the neuroprotective effect of magnolol in diabetes, there are many reports about its positive effect on the functioning of the nervous system [ 15 , 16 , 18 ]. Magnolol in in vivo studies on animal models showed a protective effect in Parkinson’s disease [ 65 ] and Alzheimer’s disease [ 66 ], supported the processes of concentration and learning and improved memory [ 66 , 67 ], or revealed antidepressant activity [ 68 , 69 ].…”
Section: Magnolol In Diabetes and Its Complicationsmentioning
confidence: 99%
See 1 more Smart Citation